Proses Pembiayaan KUR di BSI: Studi Kasus pada Divisi Mikro BSI Kraksaan - Frasasti, Meilinda (Maliki Interdisciplinary Journal, 2026)
Sharia banking plays a crucial role in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in providing access to capital. This study aims to analyze the financing process for Sharia People’s Business Credit (KUR) at Bank Syariah Indonesia (BSI) Kraksaan Branch Office. The research method used was a qualitative approach through interviews and case studies. The results indicate that the KUR Sharia financing process has been carried out systematically and in accordance with sharia principles, from the application stage to post-financing monitoring. However, increased supervision and education regarding contracts are needed to optimize financing in supporting the sustainability of MSMEs. The results of the study indicate that the KUR Sharia financing process has been carried out systematically and in accordance with sharia principles, from the application stage to post-financing monitoring. The implementation of this financing is part of the concrete efforts of Islamic banking to support the MSME ecosystem, in line with Bank Indonesia’s strategic direction for the future development of the Islamic banking sector (Arfan, 2025). Furthermore, the effectiveness of the People’s Business Credit (KUR) program at BSI KCP Kraksaan has been proven to encourage an increase in the scale of customer businesses, confirming the results of research (Jaya, 2018) which found a significant influence of People’s Business Credit (KUR) on increasing the production value of micro, small, and medium enterprises. However, increased supervision and education regarding contracts are needed to optimize financing in supporting the sustainability of MSMEs. The practical implications of this research emphasize the importance of strengthening internal banking capacity in the aspect of post-disbursement customer assistance. Thus, synergy between macro regulatory policies and micro banking implementation can be harmoniously realized to accelerate the growth of Sharia-based MSMEs.